Predicting the intention to cyberbully and cyberbullying behaviour among the undergraduate students at the International Islamic University Malaysia - Abdul Rashid, Muhammad Shawal; Mohamed, Shafizan; Tengku Mohd Azman, Tengku Aisha (Global Academic Excellence, 2017)
Abstract: This study analyses the contributing factors to cyberbullying behaviour; 397 Muslim undergraduate students participated in the study and it has yielded some interesting results. Underpinned by the theory of planned behaviour, this study found some support for the theory. Specifically, perceived social pressure (subjective norms) has been identified as the most important predictor, followed by attitudes towards cyberbullying. However, perceived behavioural control was not significantly related to the toxic behaviour. Overall, these results indicate the need to address the anti-social behaviour by related-parties and preventive measures need to be taken in order to promote pro-social behaviours in the online environment.